Language Comparison Between Swahili and Malay Languages with Semantic and Pragmatic Problems - Putri, Shintia Dwi (REiLA : Journal of Research and Innovation in Language, 2020)
The purpose of this study is to explore the similarities and differences of Malay and Kiswahili, which is better known as Swahili. This study intends to investigate the patterns of response from Malays and Kiswahili. In discussing the idea of linguistic meaning by comparing the Swahili language with Malay, this study focuses on different meanings, assuming that there will be differences regarding the discussion of meaning types that can enhance understanding and appreciation of linguistic meaning. The discussion takes a general conceptual orientation of approach that considers language to be an analysis where the analytical unit is speech acts. From a broader perspective, this article distinguishes the conceptual and associative meaning of the use of Malay and Swahili languages then begins dealing with the individual types. There are five types of meanings discussed, namely conceptual, connotative, social, affective and collocative. The results show that there are many differences between Malay and Swahili languages. The connotation is meaning that is still difficult to understand, and it is what requires the continuation of learning semantics and pragmatics because every language has a different meaning following the culture.